HUKUM DAN KEPENTINGAN MASYARAKAT (Memosisikan Hukum sebagai Penyeimbang Kepentingan Masyarakat) - Sulaiman, Eman (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2013)
Although Indonesia has over ten years into the era of legal reform have not favor the interests of the community. Law is still loaded with the interests of certain parties like the ruling. This is evident from the product law for national and local regulations for local scale. Reform of the law enforcement officials running slow when compared with the substance of the reform law. This leads to the law can not act as a counterweight to the interests of society in order to realize justice and truth.